Crafting futures with hope: Young climate activists' imaginaries in an age of crisis and uncertainty. (13th December 2021) - Spyrou, Spyros; Theodorou, Eleni; Christou, Georgina
Abstract: This article explores the future imaginaries of young climate activists in Cyprus in the light of the unfolding climate crisis and the uncertainty and urgency it engenders. We analyse young people's imagined futures and their struggles to manage fear and despair through the cultivation of a collective sense of hope which allows them to act as future‐makers and to work towards creating more just and sustainable futures. Through our empirical illustration, we also make the more general case for attending to the future as a productive temporal condition in Childhood Studies' explorations of contemporary childhoods.